Gambaran Kadar Ureum, Asam Urat, Kreatinin, dan Albumin Pasien TB-MDR yang Mengkonsumsi OAT di RSP Dr. Ario Wirawan Salatiga - Qomariyah, Nurul; Hidayah, Nur; Rahmaddina, Selma Aulia (Poltekkes Kemenkes Semarang, 2024)
Multi Drug Resistant Tuberculosis (MDR-TB) is a type of tuberculosis that is resistant to two first-line antituberculosis drugs (OAT), namely Isoniazid and Rifampicin. MDR-TB treatment involves a combination of first-line and second-line OAT, which is carried out over a long period of time. The prolonged use of these drugs can cause side effects that affect various organs of the body, especially the kidneys. One indication of impaired kidney function is an increase in blood levels of ureum, uric acid, creatinine and albumin. In addition, side effects of drugs such as Kanamycin, which is nephrotoxic, can cause accumulation in the proximal tubules of the kidneys, reduce the glomerular filtration rate, and impact creatinine levels. Another side effect that can arise during MDR-TB treatment is a decrease in appetite, which leads to decreased nutritional intake, reflected in low albumin levels. This study aims to describe the levels of ureum, uric acid, creatinine, and albumin in patients with MDR-TB undergoing treatment at Ario Wirawan Lung Hospital (RSPAW) Salatiga. This study is descriptive qualitative with a cross-sectional approach. Secondary data were collected from the medical record installation from January to December 2023. This study involved 28 respondents, of which 92.86% had normal ureum levels, 71.43% had normal uric acid levels, 96.43% had normal creatinine levels, and 78.57% had normal albumin levels. A small proportion of respondents had elevated ureum or uric acid levels, with some variation in the combination of abnormal creatinine and albumin levels. The conclusion of this study is that although there were patients with abnormal ureum, uric acid, creatinine, or albumin levels, MDR-TB treatment generally did not significantly affect ureum, uric acid, creatinine, and albumin levels in the majority of patients. However, regular monitoring of renal function and nutritional status is still required to detect and manage adverse effects that may arise during long-term treatment.